STUDI KOMPARATIF KINERJA PORTOFOLIO SAHAM KELOMPOK PER TINGGI DAN KELOMPOK PER RENDAH DI BEI - Dewi, Putu Agustina; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen; Vol 8 No 10 (2019)DO - 10.24843/EJMUNUD.2019.v08.i10.p22, 2019)
This study aims to compare the performance of the high PER group stock portfolio with the performance of the low PER group stock portfolio in the manufacturing industry listed on the Indonesia Stock Exchange. The population in this study were 141 stocks. The sample used was 132 stocks using the purposive sampling method. This study uses descriptive statistical analysis and inferential statistics, namely different tests of two independent  and dependent samples. Based on the results of the comparison sharpe index shows that the performance of the stock portfolio of the high PER group is better than the low PER group in the condition of the next ownership period. The results of different tests show no difference between the two performance of the stock portfolio. The results of this study are expected to be a consideration for stock investors and investment managers to invest in high PER stocks because it provide better performance. Keywords: price earning ratio ; single index method ; sharpe index